Supramolecular arrangements of an organometallic forming nanostructured films - Camacho, S. A. [UNESP]; Aoki, P. H. B. [UNESP]; Assis, F. F. De; Pires, A. M. [UNESP]; Oliveira, K. T. De; Constantino, C. J. L. [UNESP] (ABM, ABC, ABPol, 2014)
Organometallic materials have become subject of intensive research on distinct technological applications. The Langmuir-Blodgett (LB) and Langmuir-Schaefer (LS) techniques have proven to be suitable to address challenges inherent to organic devices, in which the film properties can be tuned at molecular level. Here, we report on the supramolecular arrangement of zinc(II)-protoporphyrin(IX) dimethyl ester (ZnPPIX-DME) using the Langmuir, LB and LS techniques, leading to nanostructured films. The π-A isotherms showed that π-π stacking interaction among ZnPPIX-DME molecules takes place at the air/water interface, favoring the formation of Langmuir films closely packed. The controlled growth of the LB and LS films was monitored via UV-Vis absorption spectroscopy, with the thickness per monolayer within 1.3 and 1.7 nm. The homogeneous topography found at microscale is no longer preserved at nanoscale, which is found rougher according to AFM data. The FTIR indicated that the ZnPPIX-DME is isotropically arranged on both LB and LS films.
Keywords: ZnPPIX-DME; Langmuir film; Langmuir-Blodgett (LB); Langmuir-Schaefer (LS)